Development of hydroxyapatite coatings on laser textured 316 LSS and Ti-6Al-4V and its electrochemical behavior in SBF solution for orthopedic applications. Issue 3 (15th February 2018) - Stango, S. Arul Xavier; Karthick, D.; Swaroop, S.; Mudali, U. Kamachi; Vijayalakshmi, U.
Abstract: The current work focused on the development of hydroxyapatite (HAP) coating on laser textured metallic implants using electrophoretic deposition. HAP was synthesized by sol-gel technique and its phase purity and surface morphology were confirmed by FT-IR, XRD and SEM analysis. 316 L SS and Ti-6Al-4V metal implants were polished and the surface was modified using Nd-YAG laser operating at a pulse interval of 10 ns at various overlapping rate of 0%, 25% and 50%. The laser treated surface was characterized for its surface roughness using surface profilometry and surface morphology. The surface roughness of the metallic implants was increased by increase in the overlapping rate. The prepared HAP powder was electrophoretically deposited on bare and laser textured Ti-6Al-4V and 316 L stainless steel followed by vacuum sintering at 300 °C for 2 h. Scratch analysis results showed an improvement in adhesion strength for the HAP coatings on laser treated specimens than untreated metal. Corrosion efficiency of the coated samples was studied in SBF solution using EIS and potentiodynamic polarization studies. The result from the corrosion experiments proved increased corrosion resistance property of laser textured coated samples when compared to bare alloy due to higher adhesion of HAP coating on the metal surface. Graphical abstract: fx1